The clinical impact of time to response in de novo accelerated‐phase chronic myeloid leukemia. Issue 10 (23rd July 2020) - Ohanian, Maro; Kantarjian, Hagop M.; Shoukier, Mahran; Dellasala, Sara; Musaelyan, Arine; Nogueras Gonzalez, Graciela M.; Jabbour, Elias; Abruzzo, Lynne; Verstovsek, Srdan; Borthakur, Gautam; Ravandi, Farhad; Garcia‐Manero, Guillermo; et al.
Abstract: We aimed to describe the impact of time to response on the outcomes of 75 patients with accelerated‐phase chronic myeloid leukemia (CML‐AP) at diagnosis. Patients had at least 1 feature of AP: blasts ≥15% (n = 2), basophils ≥20% (n = 19), platelets <100 × 10 9 /L (n = 7), cytogenetic clonal evolution (n = 34), or more than one factor (n = 13). Thirty‐three patients received imatinib; 42 received a second‐generation tyrosine kinase inhibitor (2GTKI) (19 dasatinib and 23 nilotinib). We used chi‐square and Kaplan‐Meier analyses to determine the impact of various degrees of molecular and cytogenetic response at early time points (3 and 6 months) on rates of overall cytogenetic and molecular response, overall survival (OS), event‐free survival (EFS), transformation‐free survival (TFS), and failure‐free survival (FFS). After a median follow‐up of 96 months (range: 18‐224 months), the overall rate of complete cytogenetic response was 79%, of major molecular response, 71%, and of molecular reponse (MR)4.5, 59%. Patients who achieved a major cytogenetic response (MCyR) (n = 49) at 3 months had significantly better 3‐year OS (94% vs 75%; P = .002), TFS (98% vs 73%; P  < .001), EFS (93% vs 42%; P  < .001), and FFS (83% vs 25%; P  < .001) rates than patients who did not have MCyR at 3 months. Most (67%) who eventually achieved sustained MR4.5 had achieved MCyR at 3 months. In de novo CML‐AP, early response at 3 and 6 months is a strong determinant of long‐term outcome.